Effect of Deltoid Ligament Repair on Syndesmotic Stabilization in Patients with Ankle Fractures - Kim, Dae-Wook; Choi, Hong Joon (Journal of Korean Foot and Ankle Society, 2023)
Purpose: This study aimed to evaluate the effectiveness of deltoid ligament repair on syndesmotic stabilization in patients with acute ankle fractures with ruptured deltoid and syndesmotic ligaments. Materials and Methods: The medical records of 41 patients (41 ankles) who underwent surgery for Weber type B ankle fracture with ruptured deltoid and syndesmotic ligaments were retrospectively analyzed. The mean follow-up duration was 36 months (range 18~65 months). Patients were divided into two groups: those that underwent deltoid ligament repair (the deltoid group) and those who did not (the non-deltoid group). Both groups were also divided into two subgroups, namely, the D1/S1 group, which underwent syndesmotic screw fixation, or the D2/S2 group, which did not. Medial clear space (MCS), tibiofibular clear space (TFCS), anterior fibular line (AFL) ratio, and posterior fibular line (PFL) distance were measured, and visual analog scale (VAS), American Orthopaedic Foot and Ankle Society (AOFAS), and Foot Function Index (FFI) scores were evaluated. Results: TFCS changed significantly after surgery in the D2 and S1 groups (p=0.01, p=0.03, respectively). Subgroup MCSs, TFCSs, and AFL ratios were not significantly altered by surgery in the four subgroups (p=0.82, p=0.45, p=0.25, respectively). However, postoperative PFL distances were significantly different in the D2 and S1 groups and the S1 and S2 groups (p=0.02, p=0.02, respectively). Mean TFCS decreased significantly after surgery in the D2 and S1 groups. The postoperative VAS, AOFAS scores, and FFI were not significantly dif- ferent between the subgroups (p=0.44, p=0.40, and p=0.46, respectively). Conclusion: Deltoid ligament repair seemed to restore ankle stability without addressing syndesmosis in Weber type B ankle fractures with rupture of deltoid and syndesmotic ligaments. KCI Citation Count: 0